Kegiatan Magang sebagai Tax Intern di PT Mitra Adiperkasa Tbk - Felicia Meli Fonnenti; Annisa Kanti; Fanny Anggraeni; Ricky Aprilianto Mulyana (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The Merdeka Internship Program aims to improve students' competence, experience and knowledge in the world of professional work. The Merdeka Internship Program was held at The Foodhall with the position of Tax. The work, responsibilities, and participation carried out during the Merdeka Internship Program are carrying out routine work such as equalizing PPH Article 23 and final PPH via SAP, approving PPH 23 deduction slips from vendors via the n2nb2b web. As for non-routine work, such as compiling competitors' financial statements, budgeting for store supplies, tenant sales records through MOKA, and compiling The Foodhall's stores area. The results of the internship program are carrying out a series of routine activities, project activities, and activities outside of work. From this program many things can be learned and used as provisions to enter the world of work.